Circumstances of occurrence of uterine ruptures treated in a national reference maternity department in Benin from 2015 to 2019 - Ogoudjobi, Ogourinde M.; Dangbemey, Patrice D.; Obossou, Achille A. A.; Saleh, Abdel S.; Hounnouvi, Fiacre P. D.; Tshabu-Aguemon, Christiane; Denakpo, Justin L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Uterine rupture is an obstetric disaster and a major concern for the obstetrician in an African environment because of the insufficient technical support. Objective of current study was to study the circumstances of occurrence of uterine ruptures. Methods: The study was carried out at the university clinic of obstetrics and gynecology of CNHU-HKM in Cotonou. This was a descriptive and cross-sectional study with retrospective collection from January 1, 2015 to December 31, 2019. We made an exhaustive recruitment of all the patients treated in the department for uterine rupture during the study period. The study variables were socio-demographic and clinical characteristics. Data confidentiality and the anonymity of women were respected. Results: The study involved 85 cases of uterine rupture. Patients were relatively young with a mean age of 30±15.02 years. Women profile was that of populations with unfavorable socio-economic conditions. The circumstances of discovery were multiparity equal to or greater than 4 (43.5%), scarred uterus (32.9%), non-use of partogram (97.6%), osseous dystocia (10.9%) and fetal dystocia with fetal macrosomia (21.2%) and dystocic presentation (15.3%). Conclusions: This study identified epidemiological and clinical characteristics related to the circumstances of known uterine ruptures occurrence. A preventive and anticipatory oriented approach can reduce the frequency of that obstetric tragedy, the adequate management of which is often uncertain in Benin.